Pengamatan Cacat Material Aluminium 6061 Proses Pemotongan Laser Menggunakan ESP32CAM - Nanda, Rizki Aulia; Karyadi, Karyadi; Tukino, Tukino; Suhara, Ade; Rizki, Muhammad Nuzan; Ramadhan, Muhammad Faiz; Akmal, Khafid Khaulsar (Politeknik Negeri Padang, 2024)
Using high-pressure and high-temperature laser light emission techniques, laser cutting works to cut materials in such a way that components at the laser cutting point produce cutting results. However, the current problem is that laser cutting often produces material defects including protruding parts, burnt surfaces, and pores on the laser-cut parts. Given this problem, the purpose of this study is to develop a camera capable of identifying material defects caused by laser cutting . The research method is the preparation of 6061 aluminum material, the preparation of the ESP32CAM camera, and the preparation of laser cutting parameter settings. In order to run the ESP32CAM program, C and OpenCV programming languages ​​are needed to identify items with material defects, color images, histograms, and FPS are needed. The results of the study showed that detecting defects at the highest FPS reading of 15.57 and a histogram value of 250 at the x coordinate and 950000 at the y coordinate. Eight defects in the material were found using Open CV detection on the ESP32CAM camera sample 3. From this technique it can be concluded that ESP32CAM is capable of identifying material defects caused by laser cutting.